Design of substrate integrated waveguide withMinkowski-Sierpinski fractal antenna for WBAN applications - Mustafa Mohammed Jawad; Nik Noordini Nik Abd Malik; Noor Asniza Murad; Mohd Riduan Ahmad; Mona Riza Mohd Esa; Yaqdhan Mahmood Hussein (Institute of Advanced Engineering and Science, 2020)
This paper presents a new design of patch antenna using Minkowski-Sierpinski fractal technique with substrate integrated waveguide (SIW) to resonate at 60 GHz. The antenna is proposed to be used for wireless body area network applications (WBAN). The proposed antenna is implemented using Rogers 5880 substrate with permittivity of (εr) of 2.2 and loss tangent is 0.0004, height of the substrate is 0.381 mm. Computer simulation technology-Microwave Studio (CST-MW) is used to simulate the proposed antenna. The simulated results show a wide bandwidth of 3.5 GHz between the ranges of (58.3-61.7) GHz, with a good return loss of more than -10 dB. A simulated gain of 7.9 dB is achieved with a linear antenna efficiency of 91%. This proposed antenna is used to improve the quality of radiation pattern, bandwidth, and gain at millimetre wave (mm-Wave) band for WBAN applications.